Measuring Earwax Cortisol Concentration using a non-stressful sampling method. Issue 11 (November 2020) - Herane-Vives, Andres; Ortega, Lorena; Sandoval, Rodrigo; Young, Allan H.; Cleare, Anthony; Espinoza, Susana; Hayes, Alexander; Benöhr, Jan
Abstract: Background: "Short-term" samples are not the most appropriate for reflecting chronic cortisol concentration. Although hair is used for reflecting the systemic level of this hormone, its use as a "long-term" measure appears clinically problematic. Local and systemic stress and non-stress related factors may release cortisol that is accumulated in hair. Non-stressful earwax sampling methods may provide a more accurate specimen to measure chronic cortisol concentration. Methods: Earwax from both ears of 37 controls were extracted using a clinical procedure commonly associated with local pain. One month later, earwax from the left ear side was extracted using the same procedure, and earwax from the right ear side was more comfortably obtained, using a novel earwax self-sampling device. Participants also provided one centimetre of hair that represented the retrospective month of cortisol output, and one serum sample that reflected the effect of systemic stressors on cortisol levels. Earwax (ECC), Hair (HCC) and Serum (SCC) Cortisol Concentration were correlated and compared. Confounders' effect on cortisol levels were studied. Results: The highest levels of cortisol concentration were found in serum, and the lowest in hair (p < 0.01). Left-ECC was larger than Right-ECC (p = 0.03). Right-ECC was the only sample unaffected by confounders (all p > 0.05). A Pearson correlation showed that Right-ECC and HCC samples were moderately correlated between them (r = 0.39; p = 0.03). Conclusions: The self-sampling device did not increase cortisol locally. It provided the cortisol level that was least likely to be affected by confounding factors over the previous month. ECC using the novel device might constitute another accurate, but more suitable and affordable specimen for measuring chronic cortisol concentration. Abstract : Psychiatry; Biological psychiatry; Depression; Endocrinology; Endocrine system; Metabolism; Earwax cortisol; Serum cortisol; Hair cortisol; Self-sampling earwax device